Wafer-scale controlled growth of MoS2 by magnetron sputtering: from in-plane to inter-connected vertically-aligned flakes. (29th March 2023) - Wadhwa, Riya; Thapa, Sanjeev; Deswal, Sonia; Kumar, Pradeep; Kumar, Mukesh
Abstract: Recently, Molybdenum disulfide (MoS2 ) has attracted great attention due to its unique characteristics and potential applications in various fields. The advancements in the field have substantially improved at the laboratory scale however, a synthesis approach that produces large area growth of MoS2 on a wafer scale is the key requirement for the realization of commercial two-dimensional (2D) technology. Herein, we report tunable MoS2 growth with varied morphologies via radio frequency magnetron sputtering by controlling growth parameters. The controlled growth from in-plane to vertically-aligned (VA) MoS2 flakes has been achieved on a variety of substrates (Si, Si/SiO2, sapphire, quartz, and carbon fiber). Moreover, the growth of VA MoS2 is highly reproducible and is fabricated on a wafer scale. The flakes synthesized on the wafer show high uniformity, which is corroborated by the spatial mapping using Raman over the entire 2-inch Si/SiO2 wafer. The detailed morphological, structural, and spectroscopic analysis reveals the transition from in-plane MoS2 to VA MoS2 flakes. This work presents a facile approach to directly synthesize layered materials by sputtering technique on wafer scale. This paves the way for designing mass production of high-quality 2D materials, which will advance their practical applications by integration into device architectures in various fields.